Multifunctional hyperbranched prepolymers with tailored degree of methylation and methacrylation. (16th May 2023) - Neumann, Niklas; Thinius, Sascha; Abels, Gideon; Hartwig, Andreas; Koschek, Katharina; Boskamp, Laura
Abstract: A synthesis approach for multifunctional crosslinkable hyperbranched prepolymers with tailored degree of methylation and methacrylation with full conversion of all hydroxyl groups was investigated. Prepared by catalyzed esterification various methacrylate substitution degrees could be adjusted using predefined partially methylated polyglycerol-based precursors. The combination of methacrylic anhydride, triethylamine and 4-dimethylaminopyridine was proven to be beneficial for the esterification and full conversion of the remaining primary as well as secondary hydroxyl groups. NMR, IR and Raman spectroscopy were used to prove the insertion of methacrylic crosslinking groups in the polymeric backbone. The obtained prepolymers can be photopolymerized in bulk, while a higher methacrylate content leads to a higher crosslink density after UV curing resulting in higher stiffness and higher glass transition temperature. Atomistic model simulation clarified spatial structure of the crosslinked macromolecules and allowed T g predictions. Viscoelastic to ideal-viscous behaviour dominates in the obtained polymeric products with low network density. Graphical abstract: Image 1 Highlights: Methylated hyperbranched prepolymers with tailored degrees of methacrylation in a range of 5 and 26% with full conversion of hydroxyl groups. Synthesis strategy for a targeted and adjustable methacrylation. Beneficial combination of anhydride, auxiliary base, catalyst and inhibitor mixture. Decreasing methacrylation resulted in a decrease in T g as well as mechanical stiffness after UV curing.